First description of bacillary hemoglobinuria in a cattle in Minas Gerais, Brazil - Melo, Fabrício Gomes; Oliveira Junior, Carlos Augusto; Xavier, Rafael Gariglio Clark; Cruz, Diogo Soares Gonçalves; Ribeiro, Gustavo Henrique Siqueira; Lobato, Francisco Carlos Faria; Silva, Rodrigo Otávio Silveira (Brazilian Journal of Veterinary Pathology, 2022)
Bacillary hemoglobinuria (BH) is a histotoxic infection caused by Clostridium haemolyticum that affects mostly cattle parasitized with trematodes. The aim of present study was to describe an atypical case of BH in a cow without access to flooded areas and without parasitism by Fasciola hepatica. After eight days of sternal decubitus and apathy, a Nellore cow was euthanized and necropsied. During postmortem examination, mild jaundice, black urine and multifocal lesions in the liver were observed. Histopathology revealed multifocal coagulation foci of necrosis in liver and basophilic bacillary structures, which were confirmed as C. haemolyticum by bacterial isolation, PCR and sequencing techniques. This is the first description of BH in cattle in Minas Gerais state, Brazil and highlight the need for of inclusion of BH as differential diagnosis even in animals not parasitized by trematodes.